Conflict Management in Organizations - Dini Vientiany; Siti Arawiyyah Ardi; Maysa Putri Khairana Lubis; Maulana Alghopari Harahap (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2024)
Conflict management includes a series of actions and reactions that occur between perpetrators and external parties involved in a conflict. One method of conflict management is a process-oriented approach, which focuses on the way actors and outside parties communicate with each other. external sources and how they influence relevance and interpretation. The jobs of individuals and groups of workers in an organization are related to each other. In an organization, conflict is always caused by poor communication. This also applies to bad decisions, where poor communication is always the scapegoat. Conflict is not always detrimental; sometimes, they can also be profitable in the long run. However, the interactionist perspective argues that conflict should be encouraged because it can trigger change in the organization. Conflict can cause behavior to change.